2017
DOI: 10.3389/fendo.2017.00244
|View full text |Cite
|
Sign up to set email alerts
|

Longer Telomere Length and its Association with Lower Levels of C-Peptide

Abstract: BackgroundTelomeres undergo shortening with each cell division, which could be accelerated by increase obesity and is also related to endocrinology systems. In this study, we aimed to examine the complex association between telomere, C-peptide, and obesity as well as chronic inflammation in a large population-based cross-sectional survey.MethodsWe used data from a community-based population study, where around 1,382 participants were recruited and had telomere length measured. The association of telomere lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
1
1
0
1
Order By: Relevance
“…Our main finding on C-peptide is supported by a large crosssectional survey conducted on 1382 adult men and women, where a longer telomere was associated with lower C-peptide level (28). Very few studies report on this association, and none on the longitudinal link.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our main finding on C-peptide is supported by a large crosssectional survey conducted on 1382 adult men and women, where a longer telomere was associated with lower C-peptide level (28). Very few studies report on this association, and none on the longitudinal link.…”
Section: Discussionsupporting
confidence: 68%
“…Telomere shortening has been reported to occur even before the onset of type 2 diabetes, at the prediabetes or even insulin resistance stage ( 31 ), consistent with our finding. Similarly, a community-based prospective study on 1382 participants from the NHANES population found that telomere length was inversely associated with C-peptide levels, independent of obesity and inflammation status ( 28 ). Moreover, in a subset of the Offspring cohort of the Framingham Heart Study, insulin resistance and oxidative stress were both found to be independently associated with shorter telomere length ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ключевым проявлением клеточного старения является уменьшение длины теломер и достижение лимита Хейфлика. Установлено, что длина теломер коррелирует с концентрацией С-пептида в крови в норме и при метаболических нарушениях [6]. Пептид KE (Lys-Glu, Вилон) -представитель пептидных тимомиметиков, который был обнаружен в составе полипептидного комплекса Тималина.…”
Section: Abstract: Ke Peptide; Telomeres; Lymphocytes; Ageunclassified